Usefulness in small things : items from the under a fiver collection. - Colin, Kim, ....-; Hecht, Sam, ....- (New York : Rizzoli, 2010)
Everyday, low-cost, and mass-produced items gathered from around the world showcasing innovative design. This book presents a delightful collection of mass-produced objects that provide insight into the things that surround us. Common items such as nails, plugs, toothbrushes, soap, gloves, and sweets have their own function and differ in design from country to country and region to region. Some are examples of good and practical design, while others fail to fulfill their function. The collection shows an appreciation to detail by revealing how things are made and a sensitivity to the tasks people carry out, all the while keeping in mind the basic utilitarian design of these inexpensive everyday objects. The items come from a range of countries, including the United States, Japan, France, and Thailand, and were purchased from small local shops. More than design souvenirs that celebrate local culture, they all involve an idea about function-and in most cases the "designer" is unknown. The book is designed by Graphic Thought Facility and illustrated with over 150 newly commissioned photographs by Angela Moore. The objects are organized thematically, with concise captions that clarify the individual function of each item, exposing what is not always apparent from looking.